PD-1/PD-L1 Correlates With the Efficacy of the Treatment of Concurrent Chemoradiotherapy in Cervical Cancer - Zhang, Hanqun; Tan, Shisheng; Fang, Chunju; Zhang, Qi; Cao, Xue; Liu, Yuncong (Frontiers in Oncology, 2022)
Background: Cervical cancer (CC) is the third most common cancer in the world with high mortality. The programmed cell death 1 (PD-1)/(PD-1 ligand) PD-L1 has been reported to be an effective indicator in cancer development. In this study, we aim to explore the role of PD-1/PD-L1 in evaluation of concurrent chemoradiotherapy (CCRT) efficacy and prognosis in CC patients. Methods: We included 55 CC patients in this study. Immunohistochemistry and flow cytometry were employed to detect the expression of PD-1, Treg cells, CD8, and CD68 in tumor tissues and the contents of PD-1+ CD8+ T cells, PD-1+ CD4+ T cells, and PD-1+ Treg cells in peripheral blood. The relationships of these indexes with CCRT efficacy were measured by Spearman correlation analysis, overall survival (OS), and disease-free survival (DFS) of patients was analyzed by Kaplan-Meier estimator, and the diagnostic values of these indexes in CC were assessed by a receiver operating characteristic (ROC) curve. Results: The clinical effective rate of CCRT was 89.10%. The positive expressions of PD-L1, Treg cells, PD-1+ CD8+ T cells, PD-1+ CD4+ T cells, and PD-1+ Treg cells were reduced after CCRT, while the CD8 and CD68 increased. All 7 indexes had diagnostic values in evaluating CCRT efficacy, and were influencing factors of OS, DFS, and prognosis of CC patients. Conclusion: These findings indicate that PD-1/PD-L1 may be a potential indicator for the efficacy evaluation of CCRT and prognosis of CC. This study may offer potential targets for CC treatment.